Interdyscyplinarność, wielokulturowość, lingwokulturologia a komunikacja w języku obcym - Pacholczyk, Tadeusz (Studia Rossica Posnaniensia, 2018)
Interdisciplinarity is one of the contemporary lines of research in what are broadly understood as humanistic disciplines (although not only in these ones). It is reflected, among other things, in the megatrends of the 21st century, one of the most significant of which is the drive towards the transition from mono- to multiculturalism. Against such a background the contemporary issues of cultural linguistics and communication are outlined. The main thesis of the paper is that intercultural foreign communication is not a simple transfer of the knowledge of a new culture, but it consists in developing abilities to understand it, to combat prejudice and negative stereotypes with reference to one’s own culture, as well as to the foreign one which is being acquired.